Źródła ścieków dopływających do oczyszczalni w Kostrzynie nad Odrą = Sources of sewage flowing into wastewater treatment plant in Kostrzyn - Mazurkiewicz, Marta; Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In accordance with applicable laws and regulations local governments are required to ensure proper wastewater treatment. The same obligation applies to industrial plants that discharge into drains or use the industrial wastewater treatment systems. The article presents data on the quantity and quality of industrial wastewater flowing into municipal wastewater treatment plant in Kostrzyn taking into account their impact on the work of wastewater treatment plants.
Keywords: oczyszczanie ścieków; obowiązki dostawcy ścieków przemysłowych; wastewater treatment plant; obligations of suppliers of industrial